2021
DOI: 10.3390/vaccines9090995
|View full text |Cite
|
Sign up to set email alerts
|

Information Framing Effect on Public’s Intention to Receive the COVID-19 Vaccination in China

Abstract: The aims of the study were (1) to explore information framing effect on the public’s intention to receive the COVID-19 vaccination and (2) to understand the key factors influencing the intention of COVID-19 vaccinations in China. An online questionnaire survey was conducted to explore the influence of demographic characteristics, individual awareness, social relationship, risk disclosure, perceived vaccine efficacy, and protection duration under the assumptions of information framing. The results showed that (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 72 publications
3
31
0
2
Order By: Relevance
“…A study demonstrates that scarcity of vaccines reduced participants' vaccination intentions, so it is essential to ensure an adequate supply of vaccines to increase demands for vaccines [47]. Propagation of scientific knowledge related to the pandemic and vaccines should be further implemented on official online media [48], such as sharing the findings of COVID-19 vaccine-related studies (including safety and effectiveness of vaccines) and vaccine's approval process [42], dealing with negative responses to vaccines and safety issues [24]. Moreover, experts (such as doctors) and political figure endorsements may boost the public's vaccination willingness by popular science lectures on COVID-19 vaccines [24,48,49].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study demonstrates that scarcity of vaccines reduced participants' vaccination intentions, so it is essential to ensure an adequate supply of vaccines to increase demands for vaccines [47]. Propagation of scientific knowledge related to the pandemic and vaccines should be further implemented on official online media [48], such as sharing the findings of COVID-19 vaccine-related studies (including safety and effectiveness of vaccines) and vaccine's approval process [42], dealing with negative responses to vaccines and safety issues [24]. Moreover, experts (such as doctors) and political figure endorsements may boost the public's vaccination willingness by popular science lectures on COVID-19 vaccines [24,48,49].…”
Section: Discussionmentioning
confidence: 99%
“…Propagation of scientific knowledge related to the pandemic and vaccines should be further implemented on official online media [48], such as sharing the findings of COVID-19 vaccine-related studies (including safety and effectiveness of vaccines) and vaccine's approval process [42], dealing with negative responses to vaccines and safety issues [24]. Moreover, experts (such as doctors) and political figure endorsements may boost the public's vaccination willingness by popular science lectures on COVID-19 vaccines [24,48,49]. In particular, taking advantage of an educational video demonstrated a significant impact on the acceptance of vaccines in older people.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the influence of social networks alone might not be enough to lead to an intention to buy a vaccine tourism package. Peng et al [89] found that a better understanding of COVID-19 leads to an intention to take the vaccine. However, our study reveals that the young travelers who were socially influenced to learn more about vaccine tourism package tended to recommend but not adopt vaccine tourism, perhaps because of their limited budget.…”
Section: Discussionmentioning
confidence: 99%
“…However, the effects of risk information disclosure on vaccination behaviors are ambiguous. Some studies report positive relationships between provision of vaccine risk information and subsequent behavioral outcomes (51), while others observe negative associations (52,53). Therefore, additional research is needed to examine the relationship between Chinese young adults' exposure to Chinese COVID-19 vaccine-related risk information and their vaccination intentions.…”
Section: Discussionmentioning
confidence: 99%